Optimization of Measuring Points Layout around a Tunnel in the Transversely Isotropic Rock Mass - Zhizeng Zhang; Yongtao Li; Weili Yang; Shunchuan Wu; Xiaoli Liu; Bing Zhang (Shock and Vibration)
The arrangement of measuring points has a great impact on the uniqueness and accuracy of the back analysis of displacement. To explore the arrangement method of measuring points in the anisotropic rock mass, the principle of maximum displacement is applied to study the optimization of measuring points layout around a tunnel in the transversely isotropic rock mass. Firstly, the criterion of maximum displacement is deduced. Secondly, the variations of displacement with angle and radius are analyzed, respectively, and two key lateral pressure coefficients are obtained. Thirdly, some principles of measuring points arrangement are summarized according to the criterion of maximum displacement. Finally, an example is given to prove the correctness of these principles. These principles can be used to guide the arrangement of displacement measuring points in the transversely isotropic rock mass, especially suitable for shaft excavation in horizontal sedimentary rock.